Mapping Local Potential of Coastal Communities to Support Sustainable Empowerment - Ligar Abdillah; Fadli Afriandi (Jurnal Ilmu Sosial dan Humaniora, 2023)
Coastal communities are very close to natural wealth in the form of ample marine resources. In reality, coastal communities are positioned as groups that are socially, economically, and ecologically vulnerable. This vulnerability is motivated by the non-participatory empowerment of fishermen. This research aims to map the local potential of the fishing community in Pulo Sarok Village, Singkil District, Aceh Singkil Regency. This research is supported by qualitative methods to explore local communities' dynamics and map their resources. Data collection techniques used observation, in-depth interviews, and FGD (focus group discussion). Determining informants used the snowball sampling technique. Data were analyzed using the concept of local community empowerment initiated by Jim Ife and Frank Tesoriero. The findings from this research show that fishing communities consist of human resources that rely on local knowledge and local culture to utilize and preserve natural resources. The fishing community also has the skills to establish synergy with the village government to accommodate all their needs. The local community-based empowerment model is very suitable for fishermen who need traditional markets to distribute their catch. Fishermen must be positioned as the main actors in empowerment who best understand their problems and needs. Further research is highly recommended to analyze external parties who can facilitate fishing communities in implementing empowerment to achieve prosperity.